Interpretación del tratamiento químico con urea-cal en el valor nutritivo de la panca de arroz para la alimentación de rumiantes - Velasco Gaibor, Diana Victoria (2021)
The shortage of food has led to a serious problem, especially in the dry season, when our pastures do not grow, due to the lack of humidity and even the mistreatment of animals, by grazing, trampling, which is carried out by ruminants. Which has become a very serious problem for small and large producers, in the area the problems have even become irreversible, that the animals get sick and can even die. There are various products at hand that we can add to the feed of our ruminants animals, by-products that we find in the most accessible way and at low costs, even in various agricultural productions the product is given away, or in turn are discarded, due to the same ignorance, they are even burned and wasted. One of them is rice straw (Oryza sativa), which in the Ecuadorian coast as in the Guayas and Los Ríos provinces we find in large quantities, with a national production of husk rice production is 261,770 hectares, which means that there are tons of rice straw harvest residues in Ecuador. The Rice straw contains low levels of composition of micro and macro elements, with the ammonification process adding urea-lime that is carried out in a simple way improving its nutritional composition, it will increase its nutritional value of Protein% micro Kjeldahl 3.26, Fiber% 51.95, Ethereal extract% 0.48, DM% 42.56. It even helps us to increase the palatability of the animals, which will increase consumption and prevent diseases and deaths in our livestock.